Evaluation of Nutrition Knowledge of Pregnant Women before and after Nutrition Education according to Sociodemographic Characteristics - KARĞIN, DİCLE; GÜNEŞ, FATMA ESRA; SABUNCULAR, GÜLEREN; AKTAÇ, ŞULE (TAYLOR & FRANCIS INC, 2018)
The aim of this cross-sectional study is to evaluate the effect of nutrition education on nutritional knowledge levels of pregnant women. The study was undertaken on a sample of pregnant women (i = 743) attending health centers in Istanbul for prenatal care. Nutrition knowledge scores were significantly higher in posttest (23.0) than pretest (16.0) after receiving nutrition education (p < .001). Significant differences in pretest (p < .05) but not posttest (p > .05) scores were found for factors, such as education level, work status, and the number of pregnancies; significant differences in both test scores were found for age and nutrition information (p < .05). In conclusion, pregnant women need to be given adequate and appropriate nutrition education for maternal and child health according to sociodemographic characteristics.
Keywords: Pregnancy; nutritional knowledge; prenatal education; health education